Outcomes and experiences of DIALOG+ provided remotely for patients with anxiety disorders—A non-controlled pilot trial - Natividad Olivar; Fernando Luis Carbonetti; Luis Ignacio Brusco; Stefan Priebe (PLoS ONE, 2025)
Background Low-cost interventions in routine care are needed to reduce the burden of anxiety disorders. DIALOG+ is an evidence-based intervention specifically designed to make routine patient-clinician meetings in mental health care therapeutically effective. It has been shown to be beneficial in a range of studies, but so far not been tested in patients with a primary diagnosis of anxiety disorders. Methods We conducted a non-controlled pilot trial in an out-patient service in Buenos Aires, Argentina. DIALOG+ was applied five times over a six-month period. Because of the pandemic all sessions had to be delivered remotely which had not been originally planned. At baseline and after the intervention, we assessed as outcome criteria subjective quality of life on the Manchester Short Assessment of Quality of Life, general symptoms on the Brief Psychiatric Rating Scale and the objective social situation on the Social Outcomes Index. Patient experiences were explored in semi-structured interviews. Results Forty patients completed the study. All outcome criteria, quality of life (4.1±0.5 to 5.0±0.5; p<0.001), general symptoms (33.0±9.3 to 25.9±7.6; p<0.001) and the objective social situation (5.2±0.9 to 5.6±0.5; p=0.008) showed significant improvements. Patient reported largely positive experiences despite frequent technical problems with the online arrangements. Conclusions The findings suggest that DIALOG+ is feasible and beneficial for patients with anxiety disorders in routine care and that a remote delivery is a feasible realistic option for administering it. Future research should assess implementation methods and effectiveness in larger controlled trials and identify the effective mechanisms in DIALOG+. Trial Registration The trial was pre-registered (https://www.isrctn.com/ISRCTN38851969) on 16/12/2019.